Review Essay: Thinking about rights: A Review of Disability Rights - Macurdy, Allan H. (Disability Studies Quarterly, 2006)
Disability Studies is threatened by centrifugal forces that may pull it apart at the seams. As paradoxical as this may sound, the solution to maintaining Disability Studies as an independent and, indeed, coherent academic discipline is to re-contextualize Disability Studies within the broader trends in contemporary academe, the history of social movements in the USA, and the struggle for universal enfranchisement. To illustrate this point, I will: Draw connections between my own experiences with disabilities as a person, a student, an educator, and now a newcomer to Disability Studies; make comparisons to the now defunct Program in Comparative Culture at the University of California, Irvine; and, I will critique some presentations given at two recent Disability Studies conferences hosted by The Ohio State University (OSU). My purpose, however, is not to challenge these presenters' scholarship; rather, it is to illustrate the centrifugal forces that I see already at work within Disability Studies.